2010
DOI: 10.1039/c0cc03517c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electron-transfer properties of benzimidazole-functionalized ruthenium complexes for highly efficient dye-sensitized solar cells

Abstract: Novel heteroleptic ruthenium complexes--RD1, RD5, RD10 and RD11--with ligands based on benzimidazole were synthesized and characterized for application to dye-sensitized solar cells (DSSC); the remarkable performance of RD5-based DSSC is understood for its superior light-harvesting ability and slower charge-recombination kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 23 publications
1
40
0
Order By: Relevance
“…were synthesized adapting previously reported procedures (see Experimental section). The new Au(III) complex 4 was obtained in 82% yield by reaction between 1-methyl-2-(pyridin-2-yl)-benzimidazole17 in MeCN with an equimolar aqueous solution of NaAuCl4 and an excess of PF6 at room temperature (r.t.) for 3 h, and characterized by various methods. The gold complexes were tested for their AQP1 and AQP3 inhibition properties in hRBC by stopped-flow spectroscopy.…”
mentioning
confidence: 99%
“…were synthesized adapting previously reported procedures (see Experimental section). The new Au(III) complex 4 was obtained in 82% yield by reaction between 1-methyl-2-(pyridin-2-yl)-benzimidazole17 in MeCN with an equimolar aqueous solution of NaAuCl4 and an excess of PF6 at room temperature (r.t.) for 3 h, and characterized by various methods. The gold complexes were tested for their AQP1 and AQP3 inhibition properties in hRBC by stopped-flow spectroscopy.…”
mentioning
confidence: 99%
“…The library of functionalised pyridylbenzimidazole ligands L1-L9 has been obtained by nucleophilic substitution on the non-coordinated nitrogen atom of the commercially available pyridylbenzimidazole by reaction with a halogenated substituent (R-X) in the presence of a base (Scheme S1, Supplementary Materials) [21]. Several types of functional groups have been envisaged to study the influence of both the steric hindrance and the electronic effect on the biological properties of the final gold complexes.…”
Section: Synthesis and Characterization Of Au(iii) Complexesmentioning
confidence: 99%
“…They have attracted special attention due to their important biological or pharmacological properties [1][2][3][4][5][6][7][8] and their wide field of application in different areas of medicine [9][10][11][12] and agriculture 13 . It was reported that the 1,5-benzodiazepines and its derivatives present interesting pharmacological and therapeutic properties.…”
Section: Introductionmentioning
confidence: 99%